Identification of uncertainty levels of acoustic properties of biocomposites under different mounting conditions in impedance tube tests - (:unkn) unknown (INST NOISE CONTROL ENGINEERING, 2020)
Impedance tube method is widely used to measure acoustic properties of materials. Although this method yields reliable acoustic properties for soft textured materials, uncertainty levels of measured acoustic properties for hard materials, including biocomposites, can be quite large, mainly due to uncertain mounting conditions. Here, the effects of mounting conditions on the acoustic properties of biocomposites in an impedance tube are investigated. First, nominally identical biocomposite samples with a diameter equal to the inner diameter of impedance tube are manufactured and their acoustic properties are determined. As hard materials practically cause fitting problems in the impedance tube, the diameters of samples are reduced, as in practice, by small amounts and acoustic properties of modified samples are determined. Furthermore, in order to match the diameters of samples to the inner diameter of impedance tube, different materials such as tape, petroleum jelly and cotton are applied around samples to close the air gap between the samples and the tube's inner wall. All the results are compared, and the uncertainty levels caused by different mounting conditions on the acoustic properties of biocomposites are identified. The results show that the transmission loss (TL) measurements are dramatically affected by the mounting conditions while the sound absorption conditions are less sensitive to the mounting conditions. The deviations in the measured TL levels are highest for the samples with tape and wax (10-15 dB). On the other hand, the deviations in the measured sound absorption coefficients are highest for the samples with cotton and tape (1-2%). (C) 2021 Institute of Noise Control Engineering.
Keywords: SOUND-TRANSMISSION